Awarded with Economic Growth, from Weak to Strong Patent Legislation: Legal Study with Regard to China - Shaghayegh Haji Bagher Naeeni (Journal of Education and Vocational Research, 2018)
This paper provides a critical legal study on evaluation of patent system in China from the year1980, which is known as the beginning of Chinese modern intellectual property law including patent law till 2016 that China achieved third place in Patent Cooperation Treaty (PCT) internationally for the highest patent applications according to World Intellectual Property Organization (WIPO).  Moreover, researcher will go through few important push factors for Chinese patent legislator who developed stronger Patent law to attract more national and international inventors for investing in Chinese market without hesitation of their patent rights being infringed due to weak legislation. In other words, how China realized that being in the era of globalization for improving economic growth, it should consider at least minimum international standards in its own patent legislation. Hence, the method used in this paper will be purely a doctrine method, because the researcher will be conducting the critical legal study on mentioned aspects, which involves collecting of data from primary and secondary sources. The process involved in this research is a collative process. However, still there is room for improvement in current Chinese patent system, which will be discussed in this paper. All in all, the researcher concluded that concept of globalization is undeniable in national as well as the international market in order to have a reasonable economic growth for the same reason China had considered having stronger patent legislation in order to save its position in the market and also to increase its own rate of economic growth. On the other hand, the paper concludes by putting forward suggestions for modifying Chinese patent system.